Strategi Guru dalam Pengembangan Nilai Praktis Sila Ke-5 Pancasila pada Pembelajaran Tematik di Kelas Rendah Sekolah Dasar 121/I Muara Singoan - Dedek Nuranisa; Fadelina Wizola Diva; Puput Tri Rosdianah; Syahrial Syahrial; Silvina Noviyanti (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
This study aims to find out and describe how the strategies that teachers can use to develop the practical value of the fifth principle of Pancasila in the thematic learning process for first grade students at SDN 121/I Muara Singoan. This study uses a qualitative research method where data is obtained from observation, interviews and documentation techniques sourced from teachers, students, principals and parents of students. Then the data were analyzed using the data analysis technique of the Miles and Huberman model, namely reduction, presentation and conclusion. This study has the result that the strategies that have been implemented include the PAIKEM strategy, cooperative learning and inquiry, and various lectures to get students to always read, discuss. Other strategies used by teachers in instilling and developing the practical value of Pancasila, especially the principle of